Applying the SRL vs. ERL Theory to the Knowledge of Achievement Emotions in Undergraduate University Students - de la Fuente, Jesús; Martínez-Vicente, José Manuel; Peralta-Sánchez, Francisco Javier; Garzón-Umerenkova, Angélica; Vera, Manuel Mariano; Paoloni, Paola (Frontiers in Psychology, 2019)
The SRL vs ERL Theory predicts that a student’s own self-regulation and the regulatory nature of the context are factors that jointly determine the student’s level of motivational-affective variables. However, this principle has not yet been verified in the case of achievement emotions. The aim of this research was to test this prediction, with the hypothesis that students’ level of self-regulation (low-medium-high), in interaction with the regulatory nature of the teaching (low-medium-high), would determine positive or negative emotions as well as the degree of burnout/engagement. A total of 440 university students completed validated questionnaires on self-regulation; regulatory teaching; achievement emotions in class, in study and in testing situations; and on burnout/engagement. Using a quasi-experimental design by selection, ANOVAs and MANOVAs (3 x 3; 5 x 1) were carried out. The results confirmed that the level of self-regulation and the level of external regulation jointly determined university students’ level of achievement emotions, as well as their level of burnout/engagement. Based on these results, a five-level progressive scale was configured. We conclude that this scale may be useful and adequate as a heuristic or model for understanding and analyzing the type of student-teacher interaction that is taking place in the university classroom, and thereby learn the probability of stressful effects and the students’ level of emotional health.